Trimetallic Nanoparticles: Greener Synthesis and Their Applications - Nasrollahzadeh, Mahmoud; Sajjadi, Mohaddeseh; Iravani, Siavash; Varma, Rajender S (Nanomaterials (Basel, Switzerland), 2020)
Nanoparticles (NPs) and multifunctional nano-sized materials have significant applications in diverse fields, namely catalysis, sensors, optics, solar energy conversion, cancer therapy/diagnosis, and bioimaging. Trimetallic NPs have found unique catalytic, active food packaging, biomedical, antimicrobial, and sensing applications; they preserve an ever-superior level of catalytic activities and selectivity compared to monometallic and bimetallic nanomaterials. Due to these important applications, a variety of preparation routes, including hydrothermal, microemulsion, selective catalytic reduction, co-precipitation, and microwave-assisted methodologies have been reported for the syntheses of these nanomaterials. As the fabrication of nanomaterials using physicochemical methods often have hazardous and toxic impacts on the environment, there is a vital need to design innovative and well-organized eco-friendly, sustainable, and greener synthetic protocols for their assembly, by applying safer, renewable, and inexpensive materials. In this review, noteworthy recent advancements relating to the applications of trimetallic NPs and nanocomposites comprising these NPs are underscored as well as their eco-friendly and sustainable synthetic preparative options.
Keywords: nanoparticle synthesis; trimetallic nanoparticles; catalytic activities; sustainable synthesis; eco-friendly methods; green chemistry